Ocean Science Diplomacy can Be a Game Changer to Promote the Access to Marine Technology in Latin America and the Caribbean - Polejack, Andrei; Coelho, Luciana Fernandes (Frontiers in Research Metrics and Analytics, 2021)
Ocean science is central in providing evidence for the implementation of the Law of the Sea Convention, a global constitution for the ocean. Many provisions in the Convention target equitable opportunities for countries to exercise rights and obligations in managing the marine environment. Among these provisions is the transfer of marine technologies to developing countries, without which ocean science will refrain from achieving the goals defined by the Convention. Decades after the adoption of the Convention still show an unbalance between developed and developing countries in terms of access and benefit from marine technologies, preventing society at large to understand and manage the ocean based on the best available scientific knowledge. In this paper we present a perspective from Latin America and the Caribbean on marine technological gaps and needs, highlighting current issues of concern such as the legal framework, intellectual property rights and their consequences. We discuss that this interplay between science and international relations, as we frame science diplomacy, can inform on how to progress in allowing countries in this region to develop relevant research and implement the Convention. We provide concrete examples of this transfer of marine technology and ways forward, in particular in the context of the UN Decade of Ocean Science for Sustainable Development (2021-2030).